2015
DOI: 10.1016/j.lwt.2015.03.105
|View full text |Cite
|
Sign up to set email alerts
|

A chemometric processing-factor-based approach to the determination of the fates of five pesticides during apple processing

Abstract: a b s t r a c tFood safety, especially with respect to pesticide-contaminated products, has received considerable attention in recent years. In this study, the effects of food processing steps on pesticide residues in apples were analyzed on the basis of processing factors (PFs) via a chemometric approach. Based on the PFs data, the removal efficiencies of beta-cypermethrin, chlorpyrifos, tebuconazole, acetamiprid, and carbendazim were optimized using a chemometric tool equipped with a central composite design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…During juicing, the combination of supplementary procedures (washing, pressing, sterilization and enzymatic treatment) greatly helps reduce pesticide residues in the matrix. For instance, Li et al (2015) [ 198 ] obtained a 85–95% decrease of β-cypermethrin, chlorpyrifos, tebuconazole, acetamiprid and bendazim in apples matrix during juice processing. In another study, the reduction of HCB, lindane, p,p-DDT, dimethoate, profenofos and pirimiphos-methyl residues ranged from 73 to 78% during tomato juicing [ 36 ].…”
Section: Processing On Pesticide Residues Reductionmentioning
confidence: 99%
“…During juicing, the combination of supplementary procedures (washing, pressing, sterilization and enzymatic treatment) greatly helps reduce pesticide residues in the matrix. For instance, Li et al (2015) [ 198 ] obtained a 85–95% decrease of β-cypermethrin, chlorpyrifos, tebuconazole, acetamiprid and bendazim in apples matrix during juice processing. In another study, the reduction of HCB, lindane, p,p-DDT, dimethoate, profenofos and pirimiphos-methyl residues ranged from 73 to 78% during tomato juicing [ 36 ].…”
Section: Processing On Pesticide Residues Reductionmentioning
confidence: 99%
“…Therefore, it is concluded that peeling before consuming fruits is a more effective variable than fruit storage at 4 °C in the refrigerator due to decreasing higher studied insecticides residues. An 85–95% decrease of CPF in apples is reported during juice processing ( Li et al, 2015 ). It is concluded that utilizing appropriate doses of seed, fertilizer, and pesticides leads to decreasing studied pesticides residues in fruits, especially orange.…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms must adapt to the environment to exhibit efficient metabolism, which in turn depends on access to nutritional sources and the possibility of their use. The residues used in this study could contain substances that can limit the metabolism of PAB (e.g., pesticides, heavy metals, and polyphenols) (Kiczorowska et al 2006 ; Góralczyk et al 2009 ; Kaveli et al 2015 ; Li et al 2015 , 2020 ). Apart from glycerol, waste glycerine contains methanol and free fatty acids (Pawlicka-Kaczorowska and Czaczyk 2017 ), which may limit the metabolism of microorganisms, including their uptake of nutrients from the growth environment.…”
Section: Discussionmentioning
confidence: 99%